A unified pathogenesis for kidney diseases, including genetic diseases and cancers, by the protein-homeostasis-system hypothesis - Kyung-Yil Lee (The Korean Society of Nephrology, 2017)
Every cell of an organism is separated and protected by a cell membrane. It is proposed that harmony between intercellular communication and the health of an organism is controlled by a system, designated the protein-homeostasis-system (PHS). Kidneys consist of a variety of types of renal cells, each with its own characteristic cell-receptor interactions and producing characteristic proteins. A functional union of these renal cells can be determined by various renal function tests, and harmonious intercellular communication is essential for the healthy state of the host. Injury to a kind of renal cells can impair renal function and induce an imbalance in total body health. Every acute or chronic renal disease has unknown etiologic substances that are responsible for renal cell injury at the molecular level. The immune/repair system of the host should control the etiologic substances acting against renal cells; if this system fails, the disease progresses to end stage renal disease. Each renal disease has its characteristic pathologic lesions where immune cells and immune proteins, such as immunoglobulins and complements, are infiltrated. These immune cells and immune proteins may control the etiologic substances involved in renal pathologic lesions. Also, genetic renal diseases and cancers may originate from a protein deficiency or malfunctioning protein under the PHS. A unified pathogenesis for renal diseases, including acute glomerulonephritis, idiopathic nephrotic syndrome, immunoglobulin A nephropathy, genetic renal diseases such as Alport syndrome, and malignancies such as Wilms tumor and renal cell carcinoma, is proposed using the PHS hypothesis.